SCIENTIFIC AND RESEARCH WORK IN THE PRACTICAL TRAINING OF THE FUTURE COMPUTER SCIENCE TEACHER - Kobilskaya, Elena; Nabok, Tetiana; Demyanchenko, Olga; Lyashenko, Viktor; Bryl, Tetiana (Physical and Mathematical Education, 2022)
The interrelationship between practical and research training of students of higher education specialty "Secondary Education (Informatics)" and their influence on the formation of the components of the professional competence of the future teacher is shown. The scientific and research work during the pedagogical practice in the educational process of training students of the "Secondary Education (Informatics)" specialty as part of their professional training was analyzed.Formulation of the problem. Scientific and research competence is part of the professional competence of the future computer science teacher and the key to the formation of his worldview during his life. The relationship between practical and research training of future computer science teachers is the basis of forming the professional competence of a computer science teacher. To understand the importance of such a relationship, one should look for "points of contact" between research and practical training, in particular during production practice.Materials and methods. The following methods were used in the research process: theoretical (analysis of scientific and methodological literature on the research topic); empirical (observation and analysis of KrNU students' reports on industrial (pedagogical) practice in high school of general secondary education institutions).Results. Proposed tasks related to research work, which must be completed as part of practical training by students of the "Secondary Education (Informatics)" specialty, in particular, during industrial (pedagogical) practice in high school or general secondary education institutions.Conclusions. It is shown that research competence is the key to the formation the readiness of future informatics teachers to organize research work in institutions of general secondary education, during classroom work and optional classes in order to prepare talented students to participate in scientific competitions of the National Academy of Sciences and Olympiads. The idea put forward in the work on the formation of scientific and research competence in future teachers in close connection with practical activities will contribute to the education of a modern competitive teacher who strives to learn and improve constantly. It was concluded that pedagogical practice combined with research activity contributes to students' formation of a creative, research approach to the organization of pedagogical activity, their acquisition of the skills to conduct scientific research using effective methods and methods of pedagogical research, as well as the ability to self-monitor and self-analyze.
Keywords: research work; practical teacher training; master's thesis; research competence; professional competence